2023
DOI: 10.3390/bioengineering10101120
|View full text |Cite
|
Sign up to set email alerts
|

Application of Deep Learning for Prediction of Alzheimer’s Disease in PET/MR Imaging

Yan Zhao,
Qianrui Guo,
Yukun Zhang
et al.

Abstract: Alzheimer’s disease (AD) is a progressive neurodegenerative disorder that affects millions of people worldwide. Positron emission tomography/magnetic resonance (PET/MR) imaging is a promising technique that combines the advantages of PET and MR to provide both functional and structural information of the brain. Deep learning (DL) is a subfield of machine learning (ML) and artificial intelligence (AI) that focuses on developing algorithms and models inspired by the structure and function of the human brain’s ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 97 publications
(87 reference statements)
0
1
0
Order By: Relevance
“…More in-depth discussions surrounding artificial intelligence (AI) and machine learning (ML) were present across all article types within this review [ 78 , 79 , 80 ]. Zhou et al and Minoshima et al summarized the common ML techniques used in radiology such as feed-forward neural networks (FFNN) and convolutional neural networks (CNN) [ 78 , 79 ]. This work showed that most AI studies in hybrid imaging employ a CNN or generative adversarial network (GAN) as a part of the classification model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More in-depth discussions surrounding artificial intelligence (AI) and machine learning (ML) were present across all article types within this review [ 78 , 79 , 80 ]. Zhou et al and Minoshima et al summarized the common ML techniques used in radiology such as feed-forward neural networks (FFNN) and convolutional neural networks (CNN) [ 78 , 79 ]. This work showed that most AI studies in hybrid imaging employ a CNN or generative adversarial network (GAN) as a part of the classification model.…”
Section: Discussionmentioning
confidence: 99%
“…More in-depth discussions surrounding artificial intelligence (AI) and machine learning (ML) were present across all article types within this review [78][79][80]. Zhou et al and Minoshima et al summarized the common ML techniques used in radiology such as feed-forward neural networks (FFNN) and convolutional neural networks (CNN) [78,79].…”
Section: Artificial Intelligencementioning
confidence: 99%
“…It could be used for all phases of Alzheimer's disease as well as to differentiate between healthy people and the ill. Additionally, MRI could be utilized for the detection of mild cognitive impairment (MCI) and Alzheimer's disease (AD), as well as the conversion from MCI to AD. It can also be used to distinguish between distinct forms of dementia, such as frontotemporal dementia and AD, which may exhibit similar clinical symptoms [6,7].…”
Section: Introductionmentioning
confidence: 99%